2014
DOI: 10.1007/978-3-662-43826-8_6
|View full text |Cite
|
Sign up to set email alerts
|

A Pre-processing Composition for Secret Key Recovery on Android Smartphone

Abstract: Simple Side-Channel Analyses (SSCA) are known as techniques to uncover a cryptographic secret from one single spied waveform. Up to now, these very powerful attacks have been illustrated on simple devices which leakage was obvious. On more advanced targets, such as high-end processors of smartphones, a simple visual analysis of the waveforms might not be sufficient to read the secret at once. In this paper, we detail and explain how a composition of time-frequency pre-processings manages to extract the relevan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 14 publications
0
15
0
Order By: Relevance
“…Gebotys et al [50] demonstrated attacks on software implementations of the Advanced Encryption Standard (AES) and Elliptic Curve Cryptography (ECC) on Java-based PDAs. Later on, Nakano et al [51] attacked ECC and RSA implementations of the default crypto provider (JCE) on Android smartphones, Goller and Sigl [52] attacked RSA implementations on Android, and Belgarric et al [53] attacked the Elliptic Curve Digital Signature Algorithm (ECDSA) implementation of Android's Bouncy Castle. In a similar manner, Genkin et al [54] attacked the OpenSSL implementation of ECDSA on Android and the CommonCrypto implementation of ECDSA on iOS, respectively.…”
Section: A Passive Attacksmentioning
confidence: 99%
“…Gebotys et al [50] demonstrated attacks on software implementations of the Advanced Encryption Standard (AES) and Elliptic Curve Cryptography (ECC) on Java-based PDAs. Later on, Nakano et al [51] attacked ECC and RSA implementations of the default crypto provider (JCE) on Android smartphones, Goller and Sigl [52] attacked RSA implementations on Android, and Belgarric et al [53] attacked the Elliptic Curve Digital Signature Algorithm (ECDSA) implementation of Android's Bouncy Castle. In a similar manner, Genkin et al [54] attacked the OpenSSL implementation of ECDSA on Android and the CommonCrypto implementation of ECDSA on iOS, respectively.…”
Section: A Passive Attacksmentioning
confidence: 99%
“…Using invasive access to the device, it is possible to acquire electromagnetic and power measurements with very high fidelity in terms of bandwidth, noise and spatial locality. Such invasive access has been used for key extraction attacks on intentionallynaive RSA implementations [33,45]. A non-invasive attack was shown by Kenworthy and Rohatgi [4,38] on BouncyCastle's RSA implementation running on a smartphone.…”
Section: Overviewmentioning
confidence: 99%
“…There are three stages at which the EM data can be analysed [31]. Stage one is to compute the Fast Fourier Transform (FFT) over the baseband waveform.…”
Section: Discussionmentioning
confidence: 99%
“…Nakano et al [31] attacked an Android smartphone using low frequency attacks. The smartphone ran at 832 MHz.…”
Section: Electromagnetic Attacksmentioning
confidence: 99%
See 1 more Smart Citation